Efektifitas Penurunan Kadar Kafein pada Teh Hitam dengan Metode Ekstraksi - Iqbal Akbar Asfar, Andi Muhamad (INTEK: Jurnal Penelitian, 2017)
Black tea is a tea that is currently the most widely consumed by the people of Indonesia. Consumption of black tea more than two cups per day can affect in human healthy because tea contains 20-90 mg of caffeine per cup, while the maximum consumption of caffeine is 150 mg per day and the maximum limit of caffeine is 0.02% in food and beverages. The method used in this study is the method of soxhlet extraction by varying the ethyl alcohol as solvent are 10%, 20%, 30%, 40%, and 50% with 2.5 hours extraction time. The initial caffeine content in black tea samples was 3.97%, after extraction decreased significantly levels of caffeine on 50% ethyl alcohol concentration is 0,0199%. The extraction method using Soxhlet technique is very effective to reduce caffeine in black tea.